2015
DOI: 10.1111/omi.12133
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LtxA toxicity by blocking cholesterol binding with peptides

Abstract: Summary The leukotoxin (LtxA) produced by Aggregatibacter actinomycetemcomitans kills host immune cells, allowing the bacterium to establish an ecological niche in the upper aerodigestive tract of its human host. The interaction of LtxA with human immune cells is both complex and multifaceted, involving membrane lipids as well as cell-surface proteins. In the initial encounter with the host cell, LtxA associates with lymphocyte function-associated antigen-1 (LFA-1), a cell surface adhesion glycoprotein. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 66 publications
0
44
0
Order By: Relevance
“…The concentration used in the long-term toxicity assay is more than 2 times greater than the half-maximal inhibitory concentration (IC 50 ), found previously for CRAC 336WT inhibition of LtxA toxicity against THP-1 cells. 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration used in the long-term toxicity assay is more than 2 times greater than the half-maximal inhibitory concentration (IC 50 ), found previously for CRAC 336WT inhibition of LtxA toxicity against THP-1 cells. 23 …”
Section: Resultsmentioning
confidence: 99%
“…25 In addition, we have shown experimentally that this same peptide inhibits the activity of LtxA against target cells. 23 Here, our goal was to determine the mechanism by which the CRAC 336WT peptide interacts with membranes to understand the specific mechanism by which it inhibits LtxA activity. We found that the peptide interacts near the surface of the membrane through recognition of the hydroxyl group of Chol.…”
mentioning
confidence: 99%
“…We have previously shown that, like other bacterial toxins, e.g., (Alonso et al , 2000; Boesze-Battaglia et al , 2009; Farrand et al , 2010; Lai et al , 2013; Maxfield and Tabas, 2005; Patel et al , 2002; Schwiering et al , 2013; Zitzer et al , 2001), LtxA requires cholesterol in the plasma membrane to bind and kill target cells (Brown et al , 2013; Brown et al , 2015; Fong et al , 2006). Thus, it is possible that the cell counteracts DRAQ5 ™ -mediated decreases in the plasma membrane fluidity by decreasing the membrane cholesterol composition and that this change inhibits LtxA internalization.…”
Section: Discussionmentioning
confidence: 99%
“…LtxA toxicity requires the presence of the β 2 integrin LFA-1(LFA-1, CD11a/CD18 or α L /β 2 ) [18] and cholesterol enriched membrane domains [19,20]. LFA-1 is a native ligand for intercellular adhesion molecule (ICAM-1) located on vascular endothelial cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LFA-1 activity toward the components of the extracellular matrix is regulated by the ability of these receptors to switch between active and inactive conformations [21]. Cholesterol is essential for LtxA association with plasma membrane of human lymphocytes [19] and human monocytes [20] [26]. Binding to cholesterol is mediated by a cholesterol recognition amino acid consensus (CRAC) motif, in the N-terminal region of the toxin [19].…”
Section: Introductionmentioning
confidence: 99%